2022
DOI: 10.3390/ijms23169227
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization, and Antimicrobial Activity of Carvacrol-Loaded Zein Nanoparticles Using the pH-Driven Method

Abstract: To reduce the application of synthetic additives in the field of food preservation, this study utilized carvacrol as an antibacterial agent, and zein and sodium caseinate as carriers, to prepare composite nanoparticles loaded with carvacrol by the pH-driven method. The composite nanoparticles of zein/sodium caseinate had an excellent encapsulation efficiency (77.96~82.19%) for carvacrol, and it had remarkable redispersibility. The results of Fourier transform infrared spectroscopy showed that the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It was found that this system attacked only the pathogen of interest. Zheng et al [ 36 ] prepared carvacrol-loaded-zein nanoparticles with sodium caseinate and Bidyarany et al [ 37 ] developed carvacrol-loaded-zein nanoparticles with rhamnolipids. In both cases the antimicrobial and antifungal activity of the loaded nanoparticles was higher than that of free carvacrol.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that this system attacked only the pathogen of interest. Zheng et al [ 36 ] prepared carvacrol-loaded-zein nanoparticles with sodium caseinate and Bidyarany et al [ 37 ] developed carvacrol-loaded-zein nanoparticles with rhamnolipids. In both cases the antimicrobial and antifungal activity of the loaded nanoparticles was higher than that of free carvacrol.…”
Section: Resultsmentioning
confidence: 99%
“…Several works have used the pH‐driven method to produce protein‐ and liposome‐based nanoparticles to encapsulate CUR, quercetin, resveratrol, naringenin, naringin and carvacrol 35,37‐39 . Although the pH‐driven method is green and simple enough to encapsulate phenolic compounds by changing pH values, some phenolic compounds may not be amenable to this method 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Several works have used the pH-driven method to produce protein-and liposome-based nanoparticles to encapsulate CUR, quercetin, resveratrol, naringenin, naringin and carvacrol. 35,[37][38][39] Although the pH-driven method is green and simple enough to encapsulate phenolic compounds by changing pH values, some phenolic compounds may not be amenable to this method. 40 These compounds may be chemically unstable and insoluble under alkaline conditions; for example, pH > 9.2 resulted in significant ACN loss, and pH 8.0 caused 30% monomeric ACN degradation.…”
Section: Cur and Acn Encapsulation And Loadingmentioning
confidence: 99%
“…The pH-driven method has been widely used to prepare zein composite nanoparticles. For example, carvacrol-loaded zein/sodium caseinate composite nanoparticles were fabricated ( Zheng et al, 2022 ): the obtained particles were spherical, the particle size was around 50–200 nm, and the EE was 77.96%–82.19%. Similarly, pH-driven zein/tea saponin composite nanoparticles were developed for encapsulation and oral delivery of curcumin ( Yuan et al, 2021 ): the obtained particles were spherical, the particle size was around 100–250 nm, EE and DL were 83.73% and 22.33% respectively.…”
Section: Preparation Of Zein-based Nanoparticlesmentioning
confidence: 99%